Factors contributing job turnover at Renaissance Hotel Melaka / Nur Syamimi Mohd Bistamam - Mohd Bistamam, Nur Syamimi (Faculty of Business and Management, 2012)
These days, there are a more of researches about factors of company’s job turnover had been initiate. The intention of this study is to identify factors contributing job turnover at Renaissance Hotel Melaka. Specific objectives are to determine the most influence factors that contribute to the employee’s job stress in the organization. All employees in Renaissance Hotel Melaka were randomly selected. The questionnaire was sent to 70 respondents who are the permanent staffs at Renaissance Hotel Melaka. Statistical analysis includes descriptive analysis, reliability test, correlation analysis, regression and coefficient analysis statistic. The data then analysed using Statistical Program for Social Science (SPSS) Program. The study finds that job satisfaction and remuneration is perfect negative correlated with high turnover. Meanwhile, work environment have weak positive correlation. It is hope that the result resulted from this study would allow organization to determine factors that contribute to company’s high turnover and to avoid the problem from being worse and can influence the efficiency of the employee’s itself.